GARCINIA MANGOSTANA L. RIND EXTRACT AND PHYSICAL TRAINING REDUCE OXIDATIVE STRESS IN WISTAR RATS DURING MAXIMAL PHYSICAL ACTIVITY - Arsana, I N.; Adiputra, N.; Pangkahila, J. A.; Putra-Manuaba, and I. B. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol 7 No 2 (2013): IJBS Vol2 No2, 2013)
Oxidative stress is a condition of imbalance between the production of free radicals or reactive oxygen species (ROS) and antioxidants, in which the levels of free radicals higher than antioxidants. One causes of oxidative stress is the maximum physical activity. Oxidative stress can be reduced by antioxidants. One source of antioxidants is mangosteen rind ( Garcinia mangostana L). This study aimed to investigate the role of mangosteen rind extract and physical training in reducing Malondialdehyde (MDA, increasing Superoxide dismutase (SOD) and Glutathione Peroxidase (GPx). This study used a randomized block design with factorial pattern of 6 x 2 with four repetitions. The first treatments are mangosteen rind extract with doses; 0, 50, 100; 200; 300, and 400 mg/kg bodyweight/day for four weeks. The second treatments are the physical training consists of; without and with physical training. MDA, SOD and GPx were assessed in the end of treatment. Data were analyzed with GLZ. The results showed that average of MDA, SOD and GPx different significantly (p<0.05) after administration of extracts as well as physical training. Extracts and physical training concurrently also showed effect significant (p<0.05). However, at doses 0 until 300 mg/kg bodyweight, MDA levels more higher while SOD and GPx lower significantly (p<0.05) at training group compared with without training. Whereas at dose 400 mg/kg bw, MDA lower at training (p>0.05), while SOD and GPx were recorded significantly (p<0.05) higher than the group without training. Overall, it could be concluded that physical training with administration of mangosteen rind extract reduce oxidative stress through reduction of MDA, as well as increased both SOD and GPx.
Keywords: Garcinia mangostana L, Physical Training, oxidative stress, MDA, SOD and GPx